(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The retina is the innermost layer of the eye occupying the posterior two-third of the eye.It is a layer of photosensitive cells concerned with initial processing of visualinformation. The sensation of sight is based on a step-wise process in which light isfocused on the retina, converted to electrical impulses that are conveyed through thevisual pathways to the visual cortex of the brain where it is interpreted as a visual signal. The neurons in the retina are broadly of three types. (1) the photoreceptors, whichare located the most externally, (2) the intermediate neurons (3) the ganglion cells.